Elucidating Unique Axonal Dysfunction Between Nitrous Oxide Abuse and Vitamin B12 Deficiency - Tani, Jowy; Weng, Hsing-Yu; Chen, Hung-Ju; Chang, Tsui-San; Sung, Jia-Ying; Lin, Cindy Shin-Yi (Frontiers in Neurology, 2019)
Introduction: Abuse of nitrous oxide (N2O) has an unusually high lifetime prevalence in developed countries and represents a serious concern worldwide. Myeloneuropathy following the inhalant abuse is commonly attributed to the disturbance of vitamin B12 metabolism, with severe motor deficits are often noted. The present study aims to elucidate its underlying pathophysiology. Methods: Eighteen patients with N2O abuse or vitamin B12 deficiency were recruited. Comprehensive central and peripheral neuro-diagnostic tests were performed, including whole spine MRI, and thermal quantitative sensory testing (QST). Specifically, paired motor and sensory nerve excitability tests were performed in order to obtain a complete picture of the sensorimotor axonal damage. Results: The mean duration of N2O exposure for the N2O abuse patients was 17.13±7.23 months. MRI revealed T2 hyperintensity in 87.5% of the N2O abuse patients and 50% of the vitamin B12 deficiency patients. In N2O abuse patients, the motor nerve excitability test showed decreased in peak response (7.08±0.87 µmV, P=0.05), increased latency (7.09±0.28 ms, P<0.01), increased superexcitability (-32.95±1.74%, P<0.05), and decreased accommodation to depolarizing current (TEd(40-60ms) 56.53±0.70%, P<0.05); the sensory test showed only decreased peak response (30.54±5.98 µV, P<0.05). Meanwhile, motor test in vitamin B12 deficiency patients showed only decreased accommodation to depolarizing current (TEd(40-60ms) 55.72±1.60%, P<0.01); the sensory test showed decreased peak response (25.86±3.44 µV, P<0.05) increased superexcitability (-28.58±3.71%, P<0.001), increased subexcitability (8.31±1.64%, P<0.05), and decreased accommodation to depolarizing current (TEd(peak) 67.31±3.35%, P<0.001). Conclusion: Compared to vitamin B12 deficiency, N2O abuse patients showed prominent motor superexcitability changes and less prominent sensory superexcitability changes, hinting a unique pathological process different from that of vitamin B12 deficiency. N2O abuse might cause axonal dysfunction not only by blocking methionine metabolism but also by toxicity affecting the paranodal region.